O sujeito-comprimido - Santos, Kwame Yonatan P. [UNESP]; Dionísio, Gustavo Henrique [UNESP]; Yasui, Silvio [UNESP] (My University, 2012)
Is it possible to encapsulate in a pill the benefits of an analytical treatment? Quickly suspending the symptoms? Since the nineteenth century psychiatry has offered to the so called mentally ill "medieval forms" of treatment, as is the case of institutional admissions, the straightjacket, lobotomies, shock treatments, etc. What has changed since the mid-twentieth century advent of chlorpromazine, the first psychoactive drug, and the "psychopharmacological revolution"? Today with the Psychiatric Reform mental institutions admissions are being gradually abandoned, yet we see the rise of psychoactive drugs as protagonists in mental health treatment. This theoretical essay is an extension of a master's thesis in progress on the long-term use of psychotropic drugs. It falls within the field of mental health, specifically in the debate on the medicalization of society in contemporary processes of subjectivation of the psychiatric clinics and the treatment modalities currently offered to individuals in their suffering-existence. Thus, we seek to problematize this degrading psychiatric clinics, which produces what we call the pill-subject.

É possível encapsular em um comprimido os benefícios de tratamento analítico? Suspendendo o sintoma rapidamente? Desde o século XIX a psiquiatria vem oferecendo aos chamados doentes mentais “formas medievais” de tratamento, como é o caso das internações manicomiais, a camisa-de-força, as lobotomias, os tratamentos de choque, etc. O que mudou na metade do século XX, em que se deu a “revolução psicofarmacológica” com o aparecimento da cloropromazina, a primeira droga psicoativa? Hoje com a Reforma Psiquiátrica as intermináveis internações manicomiais estão sendo paulatinamente abandonadas, contudo vemos a ascensão dos medicamentos psicoativos, vistos como protagonistas no tratamento em Saúde Mental. O presente ensaio teórico é um desdobramento de uma pesquisa de mestrado, em andamento, sobre o uso a longo prazo de psicofármacos. Insere-se no campo da Saúde Mental, mais especificamente no debate sobre a medicalização do social no contemporâneo, seus processos de subjetivação da clínica psiquiátrica e as formas de tratamento oferecidas na atualidade aos sujeitos em seu sofrimento-existência. Assim, procura-se problematizar essa clínica psiquiátrica dessubjetivante, que produz sujeitos que podemos chamar de sujeito-comprimido.
The pill-subjects
Keywords: Medicalization; Psychotropic substances; Subjectivity; Medicalização; Psicofármacos; Subjetividade